A comprehensive study on the progressive development and applications of solar air heaters. (15th November 2021) - Goel, Varun; Hans, V.S.; Singh, Sukhmeet; Kumar, Rajneesh; Pathak, Sudhir Kumar; Singla, Mohit; Bhattacharyya, Suvanjan; Almatrafi, Eydhah; Gill, R.S.; Saini, R.P.
Highlights: To study the progressive development in solar thermal air heating systems. To study and review the possible ways to augment the performance of solar air heating systems. To review the best performing solar air heating systems along with their limitations. Abstract: The use of solar air heaters (SAH) for the collection and effective utilization of solar radiations for thermal applications is widely reported in the literature. The current article aimed to present a comprehensive literature review on history, fundamentals and the latest advancement reported in the field of solar thermal air heating systems. Various designs of solar collectors viz, evacuated tube, flat plate, multiple passages, a cross-section of the flow passage, etc. are reported and discussed. Techniques which are used for performance enhancement of SAHs such as artificial roughness, fins, baffles, vortex generators, etc. are discussed and a comparative performance assessment has been carried to identify thermohydraulic performance parameter to select the optimum configuration that can be further used for applications. A few key recommendations are also concluded from the literature for the effective design and implementation of the SAHs.